Photobiomodulation effects and applications in oncology - Faria, Clara Maria Gonçalves de (2021)
Photobiomodulation therapy employs light with low energy densities to treat several conditions, from wounds to neural diseases. The molecular basis of its effects is being unveiled, but it is stated that the cytochrome-c oxidase enzyme in mitochondria, a photon acceptor of PBMT, contributes to an increase in ATP production and modulates the reduction and oxidation of electron carriers NADH and FAD. Since its effects are not fully understood, PBMT is not used on tumors. Thus, it is interesting to investigate if its effects correlate to mitochondrial metabolism. This study indicates that PBMT decreases the redox state of oral cancer by possibly increasing glycolysis and affects normal and tumor cells through distinct pathways. Additionally, since the combination of metabolic modifications and photodynamic therapy is very attractive, the current study investigates the effects of near-infrared PBMT combined with porphyrin-based photodynamic therapy (PDT) in squamous cell carcinoma cell lines SCC-25 and SCC-4. PBMT enhanced PDT action in SCC-25 cells by increasing photosensitizer (PS) uptake and production of reactive oxygen species (ROS), while the equivalent was not seen in SCC-4 cells compared to the PDT only group. Finally, since the most successful PBMT application is in the prevention and reduction of morbidities in radiotherapy patients, such as oral mucositis, we have investigated its potential in sensitizing tumors to radiation. Here, we demonstrate its potential for skin cancer treatment using a 780-nm light source and an X-ray irradiator by showing increased DNA damage and death in cells and a 30% increase in median survival in mice. Our results indicate that the mechanism underlying these results is likely to be the modulation of the cell cycle and angiogenesis, causing an increase in necrosis when combined with radiation. Therefore, we believe the combination of PBMT and other oncological modalities is worth exploring, for its benefit-cost ratio and simple protocols, along with the possibility of improvement in treatment results.